An exploration of services and member profiles at Senior Service Centres in the Western Cape, South Africa - Harris, Fahmida (Department of Health and Rehabilitation Sciences, 2019)
Introduction The number of South Africans aged 60 years and older is increasing. The National Development Plan (NDP) aims to raise average life expectancy to 70 years by 2030. In response to similar global trends, the World Health Organization (WHO) developed the global Active Ageing Policy Framework (AAPF) to inform the actions taken by countries to address the needs of older persons, acknowledging the different contexts and cultures. The WHO recommended that the framework should have been evaluated to test its applicability and use in member countries by the first half of the twenty-first century. In South Africa, Senior Service Centres for Older persons were set up in communities to provide services to enhance the achievement of the goals of the AAPF. Unfortunately, little information is available on how the framework has been applied to inform services offered in African countries, including South Africa. This study explored services provided by Service Centres for Older Persons in the Western Cape using the WHO framework on Active Ageing as a guide to the services. The study was conducted in two phases. Aims In the first phase, the study explored the characteristics of Service Centres – the organisational structures, the types of services offered, the profile of the managers, and their perception of the needs of the members of the centres. In the second phase, the study explored the profile of the members of these centres by determining their socio-demographic profile, health and psychosocial characteristics. Methodology In phase 1, forty-one service centres were selected by stratified random sampling to proportionally represent the five districts and the Cape Metropole in the province. Only 35 service centres consented to take part in the study. In phase 2, a sample of convenience was recruited from 3 051 registered members at the 35 service centres. Only 625 members consented to participate. A cross sectional, descriptive research design was utilised to collect data on the characteristics of the service centres from the managers, using a modified self-developed questionnaire. To explore the profile of members of the service centres, a self-developed questionnaire and two standardised questionnaires namely, World Health Organization Quality of Life-BREF (WHOQOL-BREF) and World Health Organization Disability Assessment Schedule II (WHODAS II), were administered. Data analysis Descriptive statistics were used to analyse the responses to the closed-ended questions in phases 1 and 2 of the study, and data presented as frequencies. Similarly, responses to the open-ended questions were summarised and themes were identified. In phase 1, quantitative and qualitative responses were analysed according to the WHO Active Ageing Framework. In phase 2, the data generated were analysed according to the WHO International Classification of Functioning, Disability and Health Framework (ICF) model. Results Services offered to members at the centres in the six categories of determinants of the AAPF included the following: • Health and social care systems – Limited screening programs were provided as part of health promotion and disease prevention services. • Behavioural – Physical activity/exercise programmes were most common, but no programs addressed healthy eating habits, tobacco and alcohol abuse, or adherence to medication use. • Personal factors – Services were provided to enhance members’ cognitive skills. • Physical environment – No services were offered on falls prevention. • Social environment – Different types of social support programmes were offered, including meeting education and literacy needs of members through the provision of Adult Basic Education Training (ABET). • Economic – Some centres offered members opportunities for formal work and volunteering, while some provided income generation activities. Most of the managers had high school education but expressed the need for training to manage these centres. The managers perceived the needs of the members would relate to health care, social support, inactivity, isolation and safety among others. The summary of the profile of the 625 members of the centres are presented in the domains of the ICF model: • Personal factors – The members were predominantly widowed women with a mean age of 74.1 ±7.51 years (range 60–100 years). Most members displayed good lifestyle habits and engaged in various leisure and physical activities. Members were also satisfied with themselves, their health, bodily appearance and quality of life and reported a variety of aspirations for their future with and without possible future-orientated behaviours. • Health conditions – Hypertension, arthritis and diabetes were the most common health problems reported by members for which they took medication. Falls were not common among members although the majority feared falling. • Body structure and function – Most members expressed good cognitive function, could concentrate and follow conversations, and reported no hearing, visual or bladder problems. Members also reported good postural balance. • Activities and participation – Members were satisfied with their abilities to do daily activities, participate in the community, and learn new tasks. • Environmental factors – Most members resided with their children or family for various reasons, including needing care for themselves or to provide care to their children and/or extended families. Discussion and conclusion Using the WHO AAPF as a guide, it was found that services provided by Service Centres for Older Persons in the Western Cape, although varied, were deficient at most service centres. The managers responsible for providing these programmes were women with limited skills who needed more education and training to be able to manage the centres appropriately. The members of service centres, despite presenting with health challenges and multi-morbidities, indicated aspirations for the future. In view of the goals of the National Development Plan (NDP) to increase life expectancy of older persons to 70 years by 2030, a more comprehensive exploration of the profile of older persons will assist the managers of the Service Centres to respond more appropriately to the diversity of needs and interests of members.